A clinicopathological study of solitary nodule of thyroid - Dhanaram, Balaji; Arunachalam, Jothi; Muthukumaraswamy, Baskaran (International Surgery Journal, 2017)
Background: Solitary thyroid nodule is considered a challenge by surgeons and pathologists alike. Prevalence increases with age and their occurrence is spontaneous. Methods: This is a prospective study conducted in our hospital conducted over period of 2 years. About 100 patients who were confirmed as solitary nodule by clinical examination and ultrasound were included in this study and all relevant data were collected. Results: The swelling was found to be more common in women and in the age group of 20 to 30 years. The lesion was found to be benign in 92% and malignant in 8%. Out of the 8%, 4% of cases were diagnosed as malignant by FNAC. About 90% patients had undergone hemithyroidectomy and 10% underwent total thyroidectomy. The most common complication was wound infection. Conclusions: The majority of solitary nodule of thyroid was found to be benign and this clearly illustrates that hemithyroidectomy is the preferred surgery unless malignancy is suspected by fine needle aspiration cytology.